Meningkatkan Kesadaran Hukum Agar Bijak Dalam Bermedia Sosial di Citramas Kabupaten Sumedang - Fahmi Miftah Pratama; Irfan Yudiansyah (AIWADTHU: Jurnal Pengabdian Hukum, 2023)
Introduction: The existence of violations against the rule of law in using social media shows that the legal awareness of the community in using social media according to the Electronic Information and Transaction Law is still low.Purposes of Devotion: To provide knowledge to the public, especially the Perum Citramas youth group, about legal awareness in using social media wisely. Method of Devotion: The implementation method used in the realization of Counseling Counseling is carried out by the method of lectures and discussions on Mamalah State Regulations related to coastal natural resource management. This Community Service is to provide Legal Counseling to the Community about the ethics of social media, where recently there have been frequent criminal cases originating from social media. This counseling needs to be done because there are many problems that originate from the use of social media.Results of the Devotion: Implementation of eduction legal counseling activities regarding the ethics of social media for all Karang Taruna members, totaling 20 people, consisting of Karang Taruna management, Chair, Secretary and Members. Where not all Karang Taruna members understand the negative effects of social media, so that in this area there have been disputes between residents that started from misunderstandings on social media.